Answer:
x=4
Explanation:
First you need to factor the equation. You can do this by multiplying the numbers by eachother so they have a denominatior of 12.
You would come out to have this...
((x+2)*4)/12 + ((2x-4)*3)/4=3
At this point you can combine the numerators over the common denominator.
((x+2)*4+(2x-4)*3)/12=3
You can now rewrite the equation into factored form.
5x-2/6=3
Multiply both sides of the equation by 6.
5x-2=18
move the terms not containing x to the right
5x=20
and divide by 5
x=4